Drug use study for acute respiratory infection in children under 10 years of age - Iwan Dwiprahasto, Iwan Dwiprahasto (Universitas Gadjah Mada, 2005)
Background: Acute respiratory infection (ARI) is the commonest illness in children and the leading cause of morbidity and mortality in many developing countries. It comprises approximately 50 % of all illness in children under five years. Even though usually viral in origin and of a self-limiting nature, various study indicate that antibiotic prescribing for ARI is inappropriately high.Objective: This study was aimed to assess general practitioners (GPs) prescribing pattern for acute respiratory infection in children seen in private practices.Method: This study is carried out in a cross sectional study design. Participants were GPs and pharmacies in Yogyakarta Special Province. Data on patient and measure of respiratory rate were obtained from GPs office and data on prescribing were searched at all pharmacies in the province. Result: All pharmacies and 92.27% of GPs participated in the study. The average number of drug item prescribed for children with ARI was 3.74. The most widely used drugs for ARI were antibiotics followed by paracetamol, ibuprofen, chlorpheniramine maleate, phenobarbital, vitamin-C, dextromethorphan, glyceryl guaiacolate, dexamethasone, prednisone, vitamin-B6, ephedrine HCI, vitamin BI, and vitamin B2. Medication error was commonly found in the study. More than 60% children with ARI received drugs in either overdose (27.51%) or under dose (41.12%). Wrong preparation were detected in 24.07% prescriptions. It was also found that more than one fifth of children with ARI received drugs in wrong frequency of administration. Risk predictor for prescribing antibiotics were fever, abnormal respiratory rate, and duration of common cold symptom of more than 2 days.Conclusion: ARI in children was often treated unnecessarily. Medication error was also commonly found in the treatment of children with ARI visiting GPs. Physicians must be encouraged to improve their prescribing practices by always catching up with current best research evidence.Â Key words: acute respiratory infection - inappropriate prescribing - medication error - general practitioners - emergence of resistance